Community-onset Klebsiella pneumoniae pneumonia in Taiwan: clinical features of the disease and associated microbiological characteristics of isolates from pneumonia and nasopharynx - Lin, Yi-Tsung; Wang, Yu-Ping; Wang, Fu-Der; Fung, Chang-Phone (Frontiers in Microbiology, 2015)
Klebsiella pneumoniae is an important cause of community-onset pneumonia in Asian countries and South Africa. We investigated the clinical characteristics of K. pneumoniae causing community-onset pneumonia, and the associated microbiological features between K. pneumoniae isolates from pneumonia and those from the nasopharynx in Taiwan. This study was conducted at the Taipei Veterans General Hospital during July 2012 to February 2014. The clinical characteristics in patients with community-onset K. pneumoniae pneumonia were analysed. K. pneumoniae isolates from the nasopharynx of adults attending otorhinolaryngology outpatient clinics were collected to compare their microbiological features with those from pneumonia. Capsular genotypes, antimicrobial susceptibility, and multilocus sequence type (MLST) were determined among these strains. Ninety-one patients with community-onset K. pneumoniae pneumonia were enrolled. We found a high mortality (29.7%) among these patients. Capsular types K1, K2, K5, K20, K54 and K57 accounted for ~70% of the K. pneumoniae isolates causing pneumonia, and ~70% of all the K. pneumoniae strains isolated from the nasopharynx of patients in outpatient clinics. The MLST profiles further demonstrated the genetic relatedness between most pneumonia isolates and those from the nasopharynx. In conclusion, our results show that community-onset pneumonia caused by K. pneumoniae was associated with high mortality and could have a reservoir in the nasopharynx. To tackle this high-mortality disease, the distribution of capsular types and the common virulent clones in the nasopharynx might have implications for future vaccine development.